Introduction of workshop: Kick-off meeting on "Piloting and scaling of low emission development options in large scale dairy farms in China" - Zijlstra, Jelle; Dong, Hongmin (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This introduction to the kick-off meeting on "Piloting and scaling of low emission development options in large scale dairy farms in China" was presented on September 28th, 2020, by Jelle Zijlstra (WUR) and Hongmin Dong (CAAS).